Referral and counter-referral system with the management of obstetric emergencies at Hospital II-1 Moyobamba, 2020 - Cardenas-Macedo, Gissela Giovanna (2021)
The objective of the research was to know the relationship of the referral and counter-referral system with the management of obstetric emergencies at Hospital II-1 Moyobamba, 2020. Type of basic study, correlational descriptive design. The population and sample consisted of 61 obstetric references. The technique used was the documentary analysis and the data collection sheet as an instrument. Among the results, the compliance with the referral and counter-referral system is at the “Regular” level with 42%, in the same way the level of care management of obstetric patients is “Regular” with 44%, while the level of administrative management it reaches 50% of "Regular" and the most frequent diagnosis of the references is severe hypertension induced by pregnancy in 23%. Likewise, the study concluded that there is no significant relationship between the referral and counter-referral system with the management of obstetric emergencies at Hospital II-1 Moyobamba, where the Pearson Square Chi is (4,043), less than the tabular Chi with 2 degrees freedom (5.9915), indicating independence of the variables. Also, the value of sig. (Critical observed value) of 0.132> 0.05, which allows rejecting the alternative hypothesis and accepting the null hypothesis.